2021
DOI: 10.1186/s41232-021-00178-3
|View full text |Cite
|
Sign up to set email alerts
|

Transition of clinical and basic studies on liver cirrhosis treatment using cells to seek the best treatment

Abstract: The liver is a highly regenerative organ; however, its regeneration potential is reduced by chronic inflammation with fibrosis accumulation, leading to cirrhosis. With an aim to tackle liver cirrhosis, a life-threatening disease, trials of autologous bone marrow cell infusion (ABMi) therapy started in 2003. Clinical studies revealed that ABMi attenuated liver fibrosis and improved liver function in some patients; however, this therapy has some limitations such as the need of general anesthesia. Following ABMi … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…MSCs are promising cells for the regeneration of damaged tissues owing to their anti-apoptotic, cell proliferative, and immunoregulatory properties [ 19 ]. Liver cirrhosis is a life-threatening condition with decreased viable hepatocytes, and since there is no effective treatment option other than liver transplantation, regenerative therapy using MSCs has been vigorously investigated for this disease [ 22 , 30 ]. While animal studies have achieved compelling results of MSC administration for liver regeneration, the efficacy observed in current clinical studies appears to be modest and lower than expected [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…MSCs are promising cells for the regeneration of damaged tissues owing to their anti-apoptotic, cell proliferative, and immunoregulatory properties [ 19 ]. Liver cirrhosis is a life-threatening condition with decreased viable hepatocytes, and since there is no effective treatment option other than liver transplantation, regenerative therapy using MSCs has been vigorously investigated for this disease [ 22 , 30 ]. While animal studies have achieved compelling results of MSC administration for liver regeneration, the efficacy observed in current clinical studies appears to be modest and lower than expected [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Liver cirrhosis is a life-threatening condition with decreased viable hepatocytes, and since there is no effective treatment option other than liver transplantation, regenerative therapy using MSCs has been vigorously investigated for this disease [ 22 , 30 ]. While animal studies have achieved compelling results of MSC administration for liver regeneration, the efficacy observed in current clinical studies appears to be modest and lower than expected [ 22 ]. The reasons for this are still unknown, and to achieve therapeutic applications, it seems necessary to identify the molecules responsible for the regenerative effects and to elucidate the precise mechanism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the stirred bioreactor preparation method may lead to cells destruction and thus affect the immunomodulatory activity of MSCs. MSCs exert immune regulation mostly through direct cell-to-cell contact, for example, promoting phenotypic transformation of macrophages through direct cell-to-cell contact ( Terai et al, 2021 ) or by releasing cytokines through paracrine effect, such as secretion, IDO, TGF-β, and PGE2 ( Di Trapani et al, 2016 ). It can function as an immunomodulatory agent by secreting exosomes, such as the inhibition of IL-6 and TNF-α secretion through exosomes, thereby regulating the inflammatory microenvironment ( Lu et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers have suggested that MSCs injected into the body are mostly trapped in the lungs, but these MSCs can provide signals to liver macrophages as a way to reduce liver fibrosis [ 519 ]. MSCs are dependent on IL-6 and PGE2, among others, to promote the polarization of macrophages toward the anti-inflammatory M2 phenotype [ 520 , 521 ].…”
Section: Mscs For Inflammatory Liver Diseasesmentioning
confidence: 99%